1984
DOI: 10.1161/01.cir.69.5.973
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of crystalloid and blood-containing cardioplegic solutions in 60 patients.

Abstract: To determine whether adding blood to a cardioplegic solution affects myocardial preservation, a randomized prospective study was carried out in 60 patients undergoing coronary revascularization to compare the effects of crystalloid potassium cardioplegics (group C) and potassium cardioplegic solutions to which blood has been added ( 973-982, 1984. ALTHOUGH blood-containing cardioplegic solutions have been shown to provide adequate myocardial protection during periods of aortic occlusion,'-' their use in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…This conclusion correlates with the results of Buttner et al [12] who showed an almost identical paraclinical, clinical, and biochemical outcomes after surgery with blood and crystalloid cardioplegia. Thus, the beneficial effect of blood cardioplegia compared to crystalloid cardioplegia observed by others [3][4][5][6][7][8][9][10][11] must be due to other features than the oxygen carrying capacity of blood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion correlates with the results of Buttner et al [12] who showed an almost identical paraclinical, clinical, and biochemical outcomes after surgery with blood and crystalloid cardioplegia. Thus, the beneficial effect of blood cardioplegia compared to crystalloid cardioplegia observed by others [3][4][5][6][7][8][9][10][11] must be due to other features than the oxygen carrying capacity of blood.…”
Section: Discussionsupporting
confidence: 91%
“…In several of these studies, it has been suggested that addition of blood to cardioplegic solutions increases oxygen supply to the myocardium. On the other hand, a number of studies [12][13][14][15][16] show similar myocardial protective value of both cardioplegic methods. In all these studies, the cardioprotective value of the cardioplegic solutions was evaluated by hemodynamic or biochemical parameters such as systolic and diastolic function, myocardial oxygen consumption, creatine kinase myocardial band (CKMB), lactate, ATP, etc., and the myocardial oxygenation has been described only qualitatively by extrapolation of clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…Esta extração aumentou progressivamente, durante a reperfusão, embora, após 60 minutos de reperfusão, ainda fosse significantemente menor do que o controle pré-CEC. Isto pode reforçar a hipó-tese da disfunção metabólica celular, de pelo menos um grupo de células e, provavelmente, ao nível mitocondrial (9,16,23,(29)(30)(31)(32) .…”
Section: Níveis Plasmáticos Da Enzima Ck-mbunclassified
“…16 Another demonstrated that blood and crystalloid cardioplegia were similar regarding lactate metabolism after reperfusion, CK-MB release, and ventricular function. 17 The type of CCP used in these studies varied, making comparison of results difficult. Flack and colleagues 13 comparing CCP and BCP in a multicenter study, did not even differentiate subtypes of CCP.…”
Section: Discussionmentioning
confidence: 99%